Penyusunan Laporan Keuangan UMKM Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil Dan Menengah (SAK-EMKM) Study Kasus Di UMKM Kabupaten Semarang - Ristikasari, Danin; Wafa, Zaenal (Universitas Pahlawan Tuanku Tambusai, 2024)
Financial reports of UMKM1are a summary of financial information prepared during an accounting period. One of the reasons why business people of UMKM find it difficult to ignore existing standards is because of the lack of benchmarks and references in learning to manage their economic business. The Indonesian Accounting Association has prepared From January 1, 2018, new accounting standards it is being introduced to help small and medium-sized enterprises to create financialireportsimore easily. This service aims to prepare financialireports for the clothing fragrance business in Semarang district. This service uses a qualitative descriptive service method. The sources of information used consist of raw data collected by means of surveys and recorded transaction records. The results of this service serve as material for consideration of the financial reporting framework that will be implemented of UMKM with the convenience offered so as to strengthen the management of sales transactions.